(untitled) (California, 1987)
In contrast to the consensus regarding the success of postwar Japan's political and economic performance, there are widely divergent views on how Japan achieved its success and what the future holds for Japan's policy, economy, and society. With the aim of reducing the wide variety of explanations for the performance of postwar Japan's political economy and answering the major questions facing industrial nations today, nineteenth Japanese and American scholars have spent four years in joint efforts to develop the material included in these thirteen papers. The intent of this volume, and of the two companion volumes, is to provide (1) accurate and reliable descriptions of changes since 1945 - and especially since 1973 - in institutions, performance patterns, and other significant aspects of the Japanese polity and economy; (2) persuasive and balanced analyses of the reasons for the performance of the political economy of postwar Japan to date; and (3) credible and useful predictions and speculations about Japan's political economy in the years ahead...